Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Model Pembelajaran berbasis dengan Media Konkret pada Peserta Didik Kelas IV SDN-3 Telangkah Tahun Pelajaran 2016/2017: Efforts to Improve Learning Outcomes of Mathematics Using Learning Based Models with Concrete Media in Class IV Students of SDN-3 Telangkah 2016/2017 Academic Year - Repitae Repitae; Rita Rahmaniati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to: (1) describe the learning activities of students in Mathematics learning using problem-based learning models with real media; (2) improving learning outcomes of Mathematics using problem-based learning with the actual press on fourth-grade students of SDN-3 Telangkah. The method and type of research used in this study are Classroom Action Research (CAR). The subjects in this study were 32 students of grade IVA SDN-3 SDN. The data collection techniques in this study were observations and tests. While the data analysis techniques used qualitative analysis and quantitative analysis. The results of the study showed that: (1) Learning activities of students during Mathematics learning used a problem-based learning model with real media to be good. This is by observation data, namely, in the first cycle obtained an average score of 3.4 with suitable criteria. (2) There is an increase in student learning outcomes in learning activities using problem-based learning models with real media on Mathematics which shows pre-action with an average of 58 with a percentage of 47%. And there is an increase in the first cycle with an average of 92 with a rate of 100% with the classification reached.